The student leadership competencies guidebook : designing intentional leadership learning and development - Seemiller, Corey (San Francisco : Jossey-Bass, 2013)
'Bridge the gap between leadership development and career preparation! This guidebook gives leadership educators the tools they need to help students develop the competencies necessary for their chosen careers and required by their academic programs. It also offers a way to understand and demonstrate the effectiveness of leadership programs. Organized into chapters each focused on one of 60 leadership competencies common across 522 academic degree programs accredited by 97 agencies, each chapter covers: a definition and description of the competency through the lens of each of four dimensions: knowledge, value, ability, and behavior; a scenario related to college student leadership that showcases the competency in action; related competencies to help readers understand how developing one competency may also intentionally or unintentionally develop another; a correlation of the competency to the Relational Leadership Model, the Social Change Model, the Five Practices of Exemplary Leadership, and/or Emotionally Intelligent Leadership; and tangible curricular ideas to use with students to help them develop each dimension of the competency.'--
Includes bibliographical references.
Keywords: Student activities; Leadership -- Study and teaching (Higher); Interpersonal relations -- Study and teaching (Higher); Educational leadership -- Study and teaching (Higher)